Investigating the reasons behind a later or missed diagnosis of attention‐deficit/hyperactivity disorder in young people: A population cohort study - Ann John (JCPP Advances, 2024)
Background: Attention Deficit Hyperactivity Disorder (ADHD) is a common neurodevelopmental condition, more often diagnosed in males. In many individuals, particularly females, ADHD is diagnosed later or missed, the reasons for this are not fully understood. Timely diagnosis is needed to provide support, management, and treatment to improve outcomes. This study aimed to understand why some young people with ADHD experience later or missed diagnosis and to consider sex differences. Methods: This study included 9991 (females = 43.69%) individuals from the Millenium Cohort Study, a UK based population study which defined recognised ADHD by a parent‐reported clinician diagnosis, and unrecognised ADHD by parent‐reported questionnaires. Behavioural and emotional difficulties, engagement in leisure activities, and parental characteristics, were compared between those recognised earlier (by ages 5/7, n = 264, f = 19.3%) versus later (by ages 11/14, n = 260, f = 21.2%), and those recognised (n = 524, f = 20.2%) versus unrecognised (n = 1,138, f = 38.7%) using logistic regression, with odds ratios (OR) and 95% confidence intervals (CI) analysed. Sex differences were investigated with an interaction analysis. Results: Those recognised with ADHD earlier had more peer, conduct, and emotional problems, emotional dysregulation, lower cognitive ability, and poorer prosocial skills compared with those recognised later, ORs ranged from 0.27 (95% CI = 018, 0.41) to 1.20 (95% CI = 1.20, 1.32). Similar findings were seen when comparing those with recognised and unrecognised ADHD; ORs ranged from 0.11 (95% CI = 0.09, 0.15) to 1.31 (95% CI = 1.19, 1.43). Additionally, those recognised were more likely to have diagnosed autism and have less reported physical activity. Sex stratification showed that recognised males had higher emotional dysregulation than unrecognised males, but this was not seen in females. Conclusions: Our findings highlight the need to consider ADHD referral, regardless of cognitive and prosocial ability or comorbidities, if children are displaying ADHD symptoms. Additionally, symptoms of ADHD not traditionally included in screening criteria, such as emotional dysregulation, should be considered to improve gender‐inclusive recognition of ADHD.